ANALISIS POSISI KOLEKTOR DALAM GAGASAN SANENTO YULIMAN: STUDI KASUS BOOM SENI LUKIS 1980AN - Yohanes De Britto Wirajati (Canthing, 2023)
This study discusses the strengthening of the collector's position in the art world of painting after the painting boom phenomenon of the 1980s. The data to be used are the ideas of Sanento Yuliman contained in six newspaper article titles in 1990. In this study, the research question was determined to be answered, namely: What is the collector's position on reciprocal social relations in the idea of Sanento Yuliman's painting boom? What social entities influence the collector's position? Also, how is Sanento Yuliman's idea related to the response to the collector's position in the field of painting? This research using qualitative research methods, namely case studies. Based on the analysis carried out, the following conclusions are drawn: (1) Collectors are in a pattern of reciprocal social relations with galleries and sponsors, which then become a determinant in the field of painting; (2) become stronger due to the commercialization that recently emerged as a result of the art boom painting, working with requires the role of a collector; (3) the position of collectors after the painting boom and their speed in moving the field of painting with the logic of business commercialization.Keywords: collector, sanento yuliman, field of painting, boom of painting